1973
DOI: 10.1038/icb.1973.24
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Inhibitor of Lymphocyte Transformation in Serum From Patients With Chronic Renal Failure

Abstract: Summary Phytohaemagglutinin‐induced transformation of normal human lymphocytes was lower, as assessed by tritiated thymidine incorporation, in sera from patients with chronic renal failure than in normal sera. Transformation was lower in normal sera dialysed against tissue culture medium and lower still in patients’ sera similarly dialysed. Addition of patients’ sera, untreated or dialysed, to cultures of normal cells in normal serum depressed lymphocyte transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…For example, normal human lymphocytes respond less well to PHA [3, 51, mitogens [6] or allogeneic lymphocytes [7] in the presence of serum from patients with leprosy than in normal human serum. Uremic serum or plasma actively inhibits the response of normal human lymphocytes t o PHA [8,9]. It has been suggested [3] that such effects are due to overproduction of a factor, possibly a n "immunoregulatory a-globulin" [ 10, 1 I ] or "normal immunosuppressive protein" [ 121, whose normal function lies in the homeostasis of immunity, particularly cell-mediated immunity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, normal human lymphocytes respond less well to PHA [3, 51, mitogens [6] or allogeneic lymphocytes [7] in the presence of serum from patients with leprosy than in normal human serum. Uremic serum or plasma actively inhibits the response of normal human lymphocytes t o PHA [8,9]. It has been suggested [3] that such effects are due to overproduction of a factor, possibly a n "immunoregulatory a-globulin" [ 10, 1 I ] or "normal immunosuppressive protein" [ 121, whose normal function lies in the homeostasis of immunity, particularly cell-mediated immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Several observations suggest that inhibitory factors in uremic serum are responsible for the immunosuppressive effect in chronic renal failure [9,15,19,20,35], The rapid normalization of immune competence after isogeneic renal transplantation supports the hypothesis that the factors are easily excretable. The composition of 'post uremia' rat urine is now studied in our laboratory in search for soluble factors with immunosuppressive ef fects.…”
Section: Discussionmentioning
confidence: 81%
“…Other authors have found a normal in vitro cellular reactivity [12,30] and even an increased PHA stimulation responsiveness of lympho cytes from uremic patients has been reported [7,26]. Humoral factors have been proposed as a cause of im paired immune response by some [10,12,20,22,30] but not all [11] authors.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, uraemia may cause an impairment in the differentiation and maturation of thymus lymphocytes. However, there have been many reports on the suppressing activity of uraemic serum on mitogen-induced proliferation of human lymphocytes (Silk, 1967;Newberry & Sanford, 1971;Nelson & Penrose, 1973). Raskova & Morrison (1978) reported the inhibitory effect of sera from uraemic rats in the mixed lymphocyte response.…”
Section: Discussionmentioning
confidence: 99%